True and untrue and other Norse tales - Undset, Sigrid, 1882-1949; Chapman, Frederick T. (Frederick Trench), 1887-1983 (University of Minnesota Press, 2013)
A selection of Norwegian folktales, this book is based on the classic folklore collected by Pieter Christian Asbjørnsen and Jørgen Moe. These stories tell of worlds similar to our own, worlds with love and hate, sorrow and joy, humor and pathos.